PENGARUH LATIHAN VARIASI TERHADAP KEMAMPUAN PASSING BAWAH BOLAVOLI PUTERI SMA NEGERI 1 SALO KABUPATEN KAMPAR - Jamal Wahdi; Slamet Slamet; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: As for the problem with the female volleyball player in SMA 1 Salo, Kampar District, the lower passing ability of the female students still looks not optimal. Besides that hand eye coordination is also still low. The strength of the female student's arm muscles is also still not good, then the elasticity of the average wrist of the female student still looks stiff. This study aims to determine whether there is an effect of variation training on the ability to pass under the female volleyball in SMA 1 Salo, Kampar District. This research is an experimental research. The population in this study was the women’s volleyball team senior high school of Salo Kampar district which numbered 15 female student. The technique used in this study is the total sampling technique, namely the technique of determining the sample with everything in the population sampled. In this study the authors take a sample of the total population of 15 people. The training program provided is a variety of exercises given during 16 meetings held 3 times a week. The instrument of this study The test used is Passing test under volley ball. The data were analyzed using normality test and hypothesis test. After doing research using Variation Exercise Against the Ability of Passing Under volley ball female SMA Negeri 1 Salo Kampar District obtained t count = 6.983 while t table = 1.771. Where if thitung is larger than ttable then the null hypothesis is rejected. This means that there is Effect of Variation Exercise Against the Passing Skill of Lower volley ball female SMA Negeri 1 Salo district Kampar or Ha is accepted. Then the result shows there is significant influence with the improvement of ability equal to 54.20%.Keywords: Variation Exercise, Passing Down Bolavoli